The Oskillator, Artificial Force Field Highway Chauffeur - Larsson, Oskar (My University, 2020)
The fully autonomous vehicle is not here yet, but a first step would be a completely autonomous feature for a simpler subset of scenarios. In this research work, the Oskillator is presented, a combined behavior and trajectory algorithm for a Highway chauffeur based on artificial force fields. At each point in time an acceleration vector is determined by generating an artificial force based on the road and the other vehicles. The force is generated from a set of simpler force components, such as the Lane Component for centering in lane, and the Pass Component for switching lanes behind a slower vehicle, etc. The components are not additive as the logic for traffic behavior is not. Instead, a composition method was developed based on min and max operations. This way the components from different vehicles on the road prevents the influence of the others, a single car is as much an obstruction as three. The force is continuous w.r.t. all inputs and a damping is analytically determined as to avoid oscillations. The host is proven to never engage in a lane switch to a lane of another vehicle with an unsafe longitudinal distance and to stop in time to avoid crashing upon entering the unsafe longitudinal distance behind another vehicle. Experiments have been performed in a simulation environment to assess the behavior of the model. It shows that the host is able to follow the road in lane and pass when appropriate, or approach the desired headway smoothly if unable to pass. The emergent lane switching manoeuvres have a very low lateral velocity, thus the switch takes a long time. Several components could be extracted for standalone use, such as Adaptive Cruise Control or Lane Keep Assistance.
Keywords: Autonomous, Self-driving cars, Highway Chauffeur, Highway Pilot, behaviour planning, trajectory planning.